Coronary inflammation and atherosclerosis by CCTA in young adults (aged 18-45) - Annalisa Filtz; Daniel Lorenzatti; Henry A Dwaah; Carlos Espiche; Santiago F Galgani; Jake T Gilman; Alexandrina Danilov; Andrea Scotti; Piotr J Slomka; Daniel S Berman; Salim S Virani; Mario J Garcia; et al. (American Journal of Preventive Cardiology)
Structured abstract: Background: Peri-coronary adipose tissue attenuation (PCAT), a marker of coronary inflammation, is linked to coronary artery disease (CAD), but data on the role of PCAT in young individuals are limited. Aims: This study explores the interplay of PCAT and CAD by CCTA, in a symptomatic young cohort. Methods and Results: Patients aged 18–45 years without prior CAD, from Montefiore CCTA registry (2016–2022), were studied retrospectively. Atherosclerosis and PCAT of the left circumflex (LCX), left anterior descending (LAD), and right coronary artery (RCA) were measured. Youden index determined optimal PCAT thresholds for the risk of CAD, defined as presence of any coronary plaque. Multivariable logistic regression analyses assessed the relationship between PCAT and CAD. The study included 733 consecutive patients (37±5 years, 55 % women, 44 % Hispanic, 23 % non-Hispanic Black); 15 % had CAD. Patients with CAD had higher overall PCAT (-77.5 HU vs -79.5, p = 0.026). Higher PCAT was independently associated with CAD, adjusting for age, sex, BMI, smoking, hyperlipidemia, diabetes, hypertension, and family history of CAD (Adj-OR: 2.07, 95 % CI: 1.30–3.57, p = 0.009). High PCAT on LCX remained associated with CAD in CAC=0 population (Adj-OR: 3.37; 95 % CI: 1.41–8.06; p = 0.006). Adding PCAT to a multivariable model including traditional modifiable risk factors significantly improved the association with any CAD, increasing the AUC from 0.65 to 0.68 (p = 0.027). Conclusion: Coronary inflammation is associated with CAD in young patients, independently of traditional risk factors, even among patients with CAC=0 score. These findings highlight its potential as an early marker for guiding preventive strategies.